Eight new species of the genus Clubiona Latreille, 1804 from Xishuangbanna Rainforest, southwestern China (Araneae, Clubionidae) - Yu, Hao; Li, Shuqiang (Zootaxa, 2019)
Eight new species, belonging to four species groups of the genus Clubiona Latreille, 1804 are described from both males and females: C. yaoi sp. nov. from the C. apiculata species-group; C. subrama sp. nov. and C. subyaginumai sp. nov. from the C. corticalis species-group; C. quadrata sp. nov., C. subkuu sp. nov. and C. zhengi sp. nov. from the C. hystrix species-group; and C. cheni sp. nov. and C. subquebecana sp. nov. from the C. trivialis species-group. These species are currently known to occur only in Xishuangbanna Rainforest, Yunnan, China.